An evaluation of student response systems in secondary mathematics classrooms - Auliya, Risma Nurul; Sitthiworachart, Jirarat; Joy, Mike (My University, 2025)
This study aimed to determine the effects of Kahoot! and Plickers for secondary school students to improve mathematics performance and learning engagement, while also analysing students’ perceptions. This research was designed as a pre-test-post-test quasi-experimental study. 71 seventh-grade students who participated were divided into three groups: two experimental groups where Kahoot! (n = 25) and Plickers (n = 22) were deployed, and a control group (n = 24) where conventional learning was delivered. A mathematics performance test, learning engagement, and perception scale were used to collect the data. The findings showed the post-test mean scores of the mathematics performance and learning engagement were increased significantly in the three groups (p < 0.05) and the Kahoot! groups had a greater impact. Furthermore, most students had positive opinions of both Plickers and Kahoot!, noting their simplicity, creating enjoyable learning, encouraging participation, building self-confidence, keeping focus, and increasing competitiveness, although some students found them challenging, time-consuming, and presenting technical problems.
Keywords: Kahoot!; learning engagement; mathematics performance; perception; Plickers